Glypican 3 Expression in Pediatric Malignant Solid Tumors - Kinoshita, Yoshiaki; Tanaka, Sakura; Souzaki, Ryota; Miyoshi, Kina; Kohashi, Kenichi; Oda, Yoshinao; Nakatsura, Tetsuya; Taguchi, Tomoaki (European Journal of Pediatric Surgery, 2015)
Purpose Glypican 3 (GPC3) is one of the cell surface heparan sulfate proteoglycans that binds to the cell membrane, and it is known as an oncofetal protein in adult malignant tumors. Clinical trials using a GPC3 peptide vaccine have already been started in Japan as a new immunotherapy for hepatocellular carcinoma in adult patients. To investigate the possibility of GPC3 immunotherapy for pediatric malignant tumors, we assessed the expression of GPC3 in pediatric malignant tumors.Methods Immunohistochemically, the GPC3 expression was examined in 159 pediatric solid tumors, including 35 cases of neuroblastoma, 30 cases of Wilms tumor, 10 cases of hepatoblastoma, 25 cases of germ cell tumors, 56 cases of rhabdomyosarcoma, and 3 cases of other tumors. In addition, to clarify the physiological expression during the fetal to neoinfantile period, autopsy specimens of subjects without any neoplastic diseases were assessed in 9 fetal cases and 21 neoinfantile cases. The serum levels of GPC3 were also analyzed using specimens obtained from 53 subjects by the sandwich enzyme-linked immunosorbent assay method.Results Histologically, a high rate of GPC3 expression was noted in 10 (90.9%) of the 11 subjects with yolk sac tumors and 6 (60.0%) of the 10 subjects with hepatoblastoma. In addition, 9 (30.0%) of the 30 subjects with Wilms tumors and 14 (25.0%) of the 56 subjects with rhabdomyosarcoma were positive for the expression of GPC3. Concerning autopsy specimens, most of the 23 subjects younger than 7 months showed positive findings in the liver (94.7%) and kidney (81.8%). Two subjects (100%) with yolk sac tumors and six (75.0%) of the eight subjects with hepatoblastoma serologically demonstrated a high rate of positive expression. Concerning the distribution of the serum GPC3 level according to age, 8 (80.0%) of the 10 subjects younger than 1 year showed a positive finding, while only 16 (37.3%) of the 43 subjects older than 1 year showed a positive finding.Conclusion Most cases of hepatoblastoma and yolk sac tumor, and some cases of other tumors were found to express GPC3 either histologically or serologically. On the other hand, GPC3 was physiologically expressed during the fetal and neoinfantile period under 1 year of age. Although, more preliminary data and experience are required, patients older than 1 year that show a positive finding for GPC3 are considered to be appropriate candidates to receive the new immunotherapy using GPC3 peptide vaccination.
Keywords: glypican 3; tumor marker; immunotherapy